ANALISIS PRIORITAS OPERASI DAN PEMELIHARAAN SERTA REHABILITASI DAERAH IRIGASI Studi Kasus 8 Daerah Irigasi Di Daerah Istimewa Yogyakarta - , Yunita Aprilina ([Yogyakarta] : Universitas Gadjah Mada, 2013)
The governmentâs budget limitation in term of budget allocation for irrigation causes new problem due to the limited budget is not able to overcome the irrigation problems faced by many irrigation areas spread in a regency/municipality. To overcome that problem, it needs a priority analysis on operation of maintenance and rehabilitation of irrigation area to determine the irrigation areas that need handling first. Therefore, the budget distributed b3y government can be optimized. The Research conducted in 8 (eight) irrigation areas located in the Daerah Istimewa Yogyakarta irrigated areas namely Trini, Gamping, Cokrobedog, Semoyo, Kucir, Madugondo, Kuton, and Dadapan. The method used in the analysis is the method of MADM i.e SAW, WP, TOPSIS, ELECTRE and AHP. The parameters used in the research are the irrigation network conditions,water availability, area width, cultivation intensity, rice productivity,operation and maintenance cost. The irrigation systems condition parameters include dam, irrigation system, buildings, embankment and roads Inspection. Based on the analysis, The irrigation areas obtaining rehabilitation priority scale are Gamping, Cokrobedog, Madugondo, Kuton, Trini, Kucir, Dadapan and Semoyo. the parameters that relatively influenced the determination on the priority of rehabilitation are area width and irrigation network condition. MADM methods are appropriate and show consistent results in determining the order of priority based on the data obtained are WP and TOPSIS method.